POWERPOINT INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI TEKS FIKSI KELAS IV - Suryani, Mei; Widagdo, Arif (Universitas Wahid Hasyim Semarang, 2024)
The use of learning media in Bahasa Indonesia subject at SDN Langensari 04, Kabupaten Semarang, is less variation. This is due to the limited supporting media available at the school. Therefore, the researcher developed interactive PowerPoint media to improve the learning outcomes of fourth-grade students at the school. The type of research is Research and Development (R&D), which uses a qualitative approach. Data collection techniques were collected through observation, interviews, documentation, questionnaires, and tests. The research results show that the average score of 69.66 from the pretest and the posttest indicates an increase in the average student score by 90.35, with a percentage increase of 27.59% in the pretest results and 100% in the posttest. 0 students did not complete and 29 students completed, so it can be concluded that the interactive PowerPoint media is very suitable and effective for improving Bahasa Indonesia learning outcomes for fourth-grade students because the results achieved have been met.